2000
DOI: 10.1016/s0378-8741(00)00223-3
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Zingiberaceae extracts for antimicrobial and antioxidant activities

Abstract: Dichloromethane and methanol extracts of 13 Zingiberaceae species from the Alpinia, Costus and Zingiber genera were screened for antimicrobial and antioxidant activities. The antimicrobial activity of most of the extracts was antibacterial with only the methanol extract of Costus discolor showing very potent antifungal activity against only Aspergillus ochraceous (MID, 15.6 microg per disc). All the extracts showed strong antioxidant activity comparable with or higher that of alpha-tocopherol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
132
1
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(149 citation statements)
references
References 13 publications
4
132
1
5
Order By: Relevance
“…Olivaceous brown exudates appeared after 20 days of incubation at room temperature in all isolates. Zingiberaceae is the plant family which is widely distributed throughout in Southeast Asia and it presents significant resistance to both biotic and abiotic stresses (Habsah et al 2000). Z. Cassumunar is the plant in the family Zingiberaceae that is widely used in folklore remedies in many Asian countries.…”
Section: Resultsmentioning
confidence: 99%
“…Olivaceous brown exudates appeared after 20 days of incubation at room temperature in all isolates. Zingiberaceae is the plant family which is widely distributed throughout in Southeast Asia and it presents significant resistance to both biotic and abiotic stresses (Habsah et al 2000). Z. Cassumunar is the plant in the family Zingiberaceae that is widely used in folklore remedies in many Asian countries.…”
Section: Resultsmentioning
confidence: 99%
“…This is the first research study on the effects of E. elatior on lead-induced changes in serum hepatotoxicity marker enzymes and hepatic oxidative stress markers. Habsah et al (2000) reported that crude dichloromethane and methanol extracts of E. elatior possessed antioxidant activity and antitumor promoting activity. Chan et al (2008) compared 26 different species of gingers for their antioxidative properties, and they have reported that, E. elatior ranked highest in TPC and ascorbic acid equivalent antioxidant capability (AEAC).…”
Section: Discussionmentioning
confidence: 99%
“…The antibacterial action of the plant phenolic compounds is mediated through their reaction with the cell membrane, inactivation of essential enzymes and destruction or functional inactivation of genetic materials (Puupponen-Pimia et al, 2001;Vattem et al, 2004). The variety of vegetables have been investigated in an attempt to find natural antioxidants and to discover new chemical classes of antibacterial and anticancer agents (Essawi and Srour, 2000;Gnanamani et al, 2003;Habsah et al, 2000;Kudi et al, 1999;Nanasombat and Teckchuen, 2009).…”
Section: Introductionmentioning
confidence: 99%